Interaction, public and crowd (REVISTA NODO, 2019)
The use of public space implies implicitly the management of the conflict that is originated in it, many times, as emergency (that which “emerges” unexpectedly and requires a special intervention). The management of such conflicts can be addressed individually or collectively; They can also be managed from the crowd. Its future, far from confirming the alleged inconsistency of the social order confirms its validity and strength. The lability that implies is part of the mortar that builds the society, and the almost homeostatic systems of conflict management and regulation within the social, demonstrate this.
Keywords: Emergency; interaction; conflict; social order; public space